1973
DOI: 10.1037/h0035716
|View full text |Cite
|
Sign up to set email alerts
|

Effects of attention to symbolically presented rewards on self-control.

Abstract: Previous research has shown that delay of gratification is decreased when children attend to the actual rewards in the contingency during the delay period. The present study investigated the effects of attention to symbolic presentations of the contingent rewards (in the form of slide-presented images) on children's ability to wait for the delayed reward. In sharp contrast to the effect of attention to the actual rewards, attention to the symbolic contingent rewards greatly increased the duration of the childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
92
1
3

Year Published

1983
1983
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(105 citation statements)
references
References 9 publications
9
92
1
3
Order By: Relevance
“…A series of classic experiments low weight, and a case in which it is not considered at all. A series of classic experiments by psychologist Walter Mischel suggest that physical proximity is also a key determinant by psychologist Walter Mischel suggest that physical proximity is also a key determinant (for example, see Metcalfe and Mischel, 1999;Mischel and Moore, 1973). In particular, (for example, see Metcalfe and Mischel, 1999;Mischel and Moore, 1973).…”
Section: Intertemporal Choice Intertemporal Choicementioning
confidence: 99%
See 1 more Smart Citation
“…A series of classic experiments low weight, and a case in which it is not considered at all. A series of classic experiments by psychologist Walter Mischel suggest that physical proximity is also a key determinant by psychologist Walter Mischel suggest that physical proximity is also a key determinant (for example, see Metcalfe and Mischel, 1999;Mischel and Moore, 1973). In particular, (for example, see Metcalfe and Mischel, 1999;Mischel and Moore, 1973).…”
Section: Intertemporal Choice Intertemporal Choicementioning
confidence: 99%
“…A series of classic experiments by psychologist Walter Mischel suggest that physical proximity is also a key determinant by psychologist Walter Mischel suggest that physical proximity is also a key determinant (for example, see Metcalfe and Mischel, 1999;Mischel and Moore, 1973). In particular, (for example, see Metcalfe and Mischel, 1999;Mischel and Moore, 1973). In particular, Mischel investigated children's ability to postpone consumption of candy in order to Mischel investigated children's ability to postpone consumption of candy in order to get more candy and found that their ability to wait was substantially increased if the get more candy and found that their ability to wait was substantially increased if the items were not present or if they were present but covered.…”
Section: Intertemporal Choice Intertemporal Choicementioning
confidence: 99%
“…In line with the work on delay of gratification of Mischel and his colleagues (e.g., Metcalfe & Mischel, 1999;Mischel & Ayduk, 2004;Mischel, Shoda & Rodriguez, 1989), we assumed that restrained eaters are more likely than unrestrained eaters to access "hot" representations of palatable food stimuli, reflecting the arousing, 9 consummatory features of the food (i.e., its taste and texture), whereas unrestrained eaters use "cool", informational representations of food items. As Mischel's work on delay of gratification has amply demonstrated, a focus on the "hot" features of food stimuli, makes delay of gratification much more difficult (e.g., Mischel & Moore, 1973).…”
Section: The Goal Conflict Model Of Eatingmentioning
confidence: 99%
“…That is, while a positive feeling state has generally been found to in crease the probability of drawing upon positive material in memory and behaviors such as helping and generosity (Aderman, 1972;Batson, Coke, Chard, Smith, & Taliaferro, 1979;Cunningham, Steinberg, & Grev, 1980;Isen, 1970;!sen, Clark, & Schwartz, 1976;!sen & Levin, 1972;Levin & !sen, 1975;Mischel, Ebbesen, & Zeiss, 1973;Moore, Underwood, & Rosenhan, 1973;Underwood, Froming, &Moore, 1977;Weyant, 1978), the effects of negative feeling states are far more complex. Some studies suggest that in ducing negative mood states increases the likelihood of antisocial behaviors (Baron, 1972;Baron & Bell, 1975), whereas others suggest that negative affect either has no effect or increases the likelihood of positive behaviors (Carlsmith & Gross, 1969;Cialdini, Darby, & Vincent, 1973;Cialdini & Kenrick, 1976;!sen, 1970;McMillen, 1971;Mischel, Coates, & Raskoff, 1968;Mischel & Moore, 1973;D. T. Reagan, Williams, & Sparling, 1972;J.…”
Section: Discussionmentioning
confidence: 99%